Exercising woman’s basic power : a story reflection - Rima Rima; Suci Suryani (University of Muhammadiyah Purwokerto, 2022)
The purpose of this study is to disclose the sexist oppressions experienced by the female protagonist in a story, to observe the solidarity she received in going through the oppression, and to examine her personal basic power to release the oppression. This study uses a qualitative descriptive method. The method used is analyzing the source of data is in the form of the characters’ monolog, dialog, and author’s narration which are collected intensively in the short story. This study is based on the perspectives of bell hooks (1984) that elaborates sexist oppression, solidarity and personal basic power. The sexist oppressions experienced by the female protagonist in a story that is caused by the social value embedded in the patriarchy society that puts woman as the subordinate and Anita’s father is the male antagonist who shows domination over her. In the story, Anita’s husband is the male protagonist who gives his empathy to Anita to go through the oppression. The last result elaborates that solidarity obtained will support Anita to exercise her basic power. This is required to face the oppression and to release Anita from sexist oppression so that she will be able to put herself from margin to centre.